1999
DOI: 10.1029/1998ja900095
|View full text |Cite
|
Sign up to set email alerts
|

Europa and Callisto: Induced or intrinsic fields in a periodically varying plasma environment

Abstract: Abstract. Magnetometer data from four Galileo passes by the Jovian moon Europa and three passes by Callisto are used to interpret the properties of the plasma surrounding these moons and to identify internal sources of magnetic perturbations. Near Europa the measurements are consistent with a plasma rich in pickup ions whose source is freshly ionized neutrals sputtered off of the moon's surface or atmosphere. The plasma effects vary with Europa's height above the center of Jupiter's extended plasma disk. Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
228
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 198 publications
(242 citation statements)
references
References 27 publications
12
228
1
1
Order By: Relevance
“…These currents would produce a secondary (or induced) magnetic field that adds to the background field of Jupiter and to fields arising from currents flowing in the ambient plasma to give the total observed field. Khurana et al (1998) and Kivelson et al (1999) recently showed that the dominant large-scale features of magnetic field perturbations observed by the Galileo spacecraft during flybys of both Europa and Callisto are consistent with induced magnetic dipoles, as had also been pointed out by Neubauer (1998). At both moons, the observed magnetic field perturbations are approximately those expected for moons responding as perfectly conducting spheres.…”
Section: Introductionsupporting
confidence: 52%
See 4 more Smart Citations
“…These currents would produce a secondary (or induced) magnetic field that adds to the background field of Jupiter and to fields arising from currents flowing in the ambient plasma to give the total observed field. Khurana et al (1998) and Kivelson et al (1999) recently showed that the dominant large-scale features of magnetic field perturbations observed by the Galileo spacecraft during flybys of both Europa and Callisto are consistent with induced magnetic dipoles, as had also been pointed out by Neubauer (1998). At both moons, the observed magnetic field perturbations are approximately those expected for moons responding as perfectly conducting spheres.…”
Section: Introductionsupporting
confidence: 52%
“…As a result, this moon is exposed to a roughly constant field during most of the time interval between consecutive current sheet crossings (see Fig. 1b of Kivelson et al 1999). This is not the case of Europa, where the importance of the current sheet field relative to Jupiter's dipole field is small.…”
Section: The Primary Fieldmentioning
confidence: 92%
See 3 more Smart Citations